2022
DOI: 10.1002/slct.202201940
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Crystal Structures of Pb2CO4 and PbC2O5 with Tetrahedral [CO4] and Pyrocarbonate [C2O5] atomic groups

Abstract: The search of the stable intermediate compounds in the system PbO−CO2 have been performed using crystal structure prediction technique in the pressure range of 0–50 GPa. Stable structures were found for the compositions Pb2CO4 and PbC2O5. The earlier known oxy‐carbonate Pb2CO4‐P212121 was shown to transform at 10 GPa into another oxy‐carbonate Pb2CO4‐Pnma and than at 22 GPa – into the sp3‐hybridized orthocarbonate with the same symmetry. PbC2O5 became thermodynamically stable at almost 10 GPa in the form of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…Only the high-pressure phase transitions of PbCO 3 remained unexplored. In this and previous work, 6 we have confirmed that similarly to other carbonates, PbCO 3 transforms into post-aragonite at high pressure and have calculated the P−T phase diagram for this compound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the high-pressure phase transitions of PbCO 3 remained unexplored. In this and previous work, 6 we have confirmed that similarly to other carbonates, PbCO 3 transforms into post-aragonite at high pressure and have calculated the P−T phase diagram for this compound.…”
Section: Discussionmentioning
confidence: 99%
“…With a relatively small compression, ∼0.5 GPa, CaCO 3 also acquires the structure of aragonite . For CaCO 3 , SrCO 3 , and BaCO 3 , the transition from aragonite to post-aragonite is observed at 35, 15, and 10 GPa, respectively. There is no available experimental data on the transition of PbCO 3 at high enough pressures, but according to calculations, the transition from aragonite to post-aragonite is also realized for this compound and the pressure of phase transition is nearly equal to 30 GPa . Below, in some cases, in particular, in the figures, we will denote the aragonite and post-aragonite structures by their symmetry groups, Pnma and Pnnm , respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For SrC 2 O 5 , the following polymorphic transitions were found with increasing pressure: showing exotic crystallchemistry unknown at ambient pressure. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Using numerical (crystal structure prediction methods) and real experiments orthocarbonates (M 2 CO 4 compounds with isolated [CO 4 ] 4À tetrahedra), [2][3][4][5][6][7][8] oxy-orthocarbonates (M 3 CO 5 compounds with isolated [CO 4 ] 4À tetrahedra and "free" oxygen atoms) 1,2,5,9 and pyrocarbonates (MC 2 O 5 compounds with two oxygen-sharing [CO 3 ] 2À triangles) [11][12][13] were predicted and/or synthesized. Unlike socalled conventional carbonates with chemical composition MCO 3 , whose structures are characterized by the presence of isolated [CO 3 ] 2À triangles, the structures of the "new" carbonates of M 2 CO 4 , M 3 CO 5 , and MC 2 O 5 chemical compositions are characterized by the presence of the different types of bonding of [CO 4 ] 4À tetrahedra.…”
mentioning
confidence: 99%
“…In addition, the formation of polymerized [CO 3 ] 2À triangles has recently been shown. [11][12][13] Orthocarbonates (M 2 CO 4 ) and oxy-orthocarbonates (M 3 CO 5 ) are formed as a result of the reaction between a carbonate and an oxide of the corresponding element. To date, the feasibility of this reaction with the formation of orthocarbonates has been theoretically demonstrated for alkali metals (Li, Na, K, Rb, and Cs), 3,15 alkaline earth metals (Mg, Ca, Sr, and Ba), 2,4,5 and p-metal (Pb), 12 while the formation of oxy-orthocarbonates has been found only for calcium, 1,2 strontium, and barium.…”
mentioning
confidence: 99%